Efficient Deep‐Blue Electroluminescence Based on Phenanthroimidazole‐Dibenzothiophene Derivatives with Different Oxidation States of the Sulfur Atom. Issue 5 (2nd February 2017) - Tang, Xiangyang; Shan, Tong; Bai, Qing; Ma, Hongwei; He, Xin; Lu, Ping
Abstract: Developing efficient deep‐blue materials is a long‐term research focus in the field of organic light‐emitting diodes (OLEDs). In this paper, we report two deep‐blue molecules, PITO and PISF, which share similar chemical structures but exhibit different photophysical and device properties. These two molecules consist of phenanthroimidazole and dibenzothiophene analogs. The distinction of their chemical structures lies in the different oxidation states of the S atom. For PITO, the S atom is oxidized and the resulting structure dibenzothiophene S, S‐dioxide becomes electron deficient. Therefore, PITO displays remarkable solvatochromism, implying a charge‐transfer (CT) excited state formed between the donor (D) phenanthroimidazole and acceptor (A) dibenzothiophene S, S‐dioxide. For PISF, it is constituted of phenanthroimidazole and dibenzothiophene in which the S atom is not oxidized. PISF displays locally excited (LE) emission with little solvatochromism. Compared with PISF, the D–A molecule PITO with an electron‐deficient group shows a much lower LUMO energy level, which is in favor of electron injection in device. In addition, PITO exhibits more balanced carrier transport. However, PISF is capable of emitting in the shorter wavelength region, which is beneficial to obtain better color purity. The doped electroluminescence (EL) device of the D–A molecule PITO manifests deep‐blue emission with CIE coordinates of (0.15, 0.08) and maximum external quantum efficiency (EQE) of 4.67 %. The doped EL device of the LE molecule PISF, however, reveals an even bluer emission with CIE coordinates of (0.15, 0.06) and a maximum EQE of 4.08 %. Abstract : Rocking the blues : Two blue‐emitting molecules, PITO and PISF, with different oxidation states of the S atom are reported. They share similar molecular structures but exhibit different photophysical and device properties. Both the PITO and PISF‐doped devices show deep‐blue emission with a maximum external quantum efficiency of 4.67 % and 4.08 %, respectively.